Social characteristics, academic behavior, and performance of undergraduate students from the University of the Philippines Visayas (Iloilo). - Danao, Denise Maxilom (Miag-ao, Iloilo University of the Philippines Visayas, Division of Social Sciences, March, 2008)
The study described the social characteristics, academic behavior, and academic performance of 95 randomly selected college students from the University of the Philippines Visayas. Specifically, the study described the socio-demographic and economic characteristics of the students at the individual and households levels, the academic behavior, attitude of students towards their degree program and university life, and the problems that they face and the coping mechanisms that they employ. The students came from socio-demographic and economic background, had varied academic practices, had different attitudes towards their degree program and university life, and encountered varied personal and academic problems.
Thesis - Undergraduate (Bachelor of Science in Economics)- University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Social characteristics of students--University of the Philippines Visayas; Academic behavior of students--University of the Philippines Visayas